Sensitivity analysis of the channel estimation deviation to the MAP decoding algorithm - WAN Ke; FAN Ping-zhi (Tongxin xuebao)
As a necessary input parameter for MAP decoding algorithm,SNR was normally obtained from the channel estimation unit.Corresponding research indicated that SNR estimation deviation degraded significantly the performance of Turbo decoding.MAP decoding algorithm with SNR estimation deviation was investigated in details,and the degradation mechanism of Turbo decoding was explained analytically.The theoretical analysis and computer simulation have disclosed the specific reasons for the performance degradation when SNR estimation is less than the actual value,and for the higher sensitivity of SNR estimation to long frame Turbo codes.